Nephroprotective influence of ademetionine on the functional state of rats kidneys in conditions of gentamicin-induced kidney injury - I. I. Zamorskii; V. M. Drachuk (Kazimierz Wielki University, 2018)
Nowadays acute kidney injury (AKI) is considered as an issue of increased global concern as its incidence is increasing over the years despite introduction of new therapies. Every 5th case of AKI is a result of toxic influence, including nephrotoxic effects of drugs. Nephrotoxicity is one of the most important side effects of aminoglycoside antibiotics, especially gentamicin, which causes kidney damage of different degree in 25% of patients. For this reason, there is a constant search for new therapies with nephroprotective activity, able to prevent or decrease toxic kidney injury during treatment with aminoglycosides. Functional state of kidneys in conditions of gentamicin-induced AKI and use of ademetionine was studied in an experiment on white male rats. Nephroprotective effect of ademetionine resulted in amelioration of excretory and ion-regulating kidney function of animals, confirmed by an increase in diuresis, glomerular filtration rate (GRF), reduction in proteinuria, normalization of sodium and potassium balance. An established correlation between indices reflects restoration of functional activity of both proximal and distal parts of nephrons as well as maintenance of the kidney mechanisms of autoregulation. Obtained results justify further study of ademetionine as a promising nephroprotector.